2015
DOI: 10.1111/ans.12988
|View full text |Cite
|
Sign up to set email alerts
|

Mobile task management tool that improves workflow of an acute general surgical service

Abstract: Background: Understanding and being able to measure constraints within a health system is crucial if outcomes are to be improved. Current systems lack the ability to capture decision making with regard to tasks performed within a patient journey. The aim of this study was to assess the impact of a mobile task management tool on clinical workflow within an acute general surgical service by analysing data capture and usability of the application tool. Methods: The Cortex iOS application was developed to digitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Studies varied greatly in their aims, methodologies, and sample sizes. A variety of study designs were selected for analysis, including four systematic reviews (Holmen et al., ; Kitsiou, Pare, Jaana, & Gerber, ; Lee et al., ; Peiris, Praveen, Johnson, & Mogulluru, ), four randomized controlled trials (Armstrong, Coyte, Brown, Beber, & Semple, ; Cingi et al., ; Lakshminarayana et al., ; Wolf et al., ), one nonrandomized controlled trial (Sundberg et al., ), three retrospective cohort studies (Dickson, Sumathipala, & Reeves, ; Khanna, Sambandam, Gul, & Mounasamy, ; Twichell et al., ), six pilot studies (Foo et al., ; Gunter et al., ; Jakel et al., ; Macpherson et al., ; Patel, Siegler, Stromberg, Ravitz, & Hanson, ; Semple, Sharpe, Murnaghan, Theodoropoulos, & Metcalfe, ), and one case report (Gernart et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies varied greatly in their aims, methodologies, and sample sizes. A variety of study designs were selected for analysis, including four systematic reviews (Holmen et al., ; Kitsiou, Pare, Jaana, & Gerber, ; Lee et al., ; Peiris, Praveen, Johnson, & Mogulluru, ), four randomized controlled trials (Armstrong, Coyte, Brown, Beber, & Semple, ; Cingi et al., ; Lakshminarayana et al., ; Wolf et al., ), one nonrandomized controlled trial (Sundberg et al., ), three retrospective cohort studies (Dickson, Sumathipala, & Reeves, ; Khanna, Sambandam, Gul, & Mounasamy, ; Twichell et al., ), six pilot studies (Foo et al., ; Gunter et al., ; Jakel et al., ; Macpherson et al., ; Patel, Siegler, Stromberg, Ravitz, & Hanson, ; Semple, Sharpe, Murnaghan, Theodoropoulos, & Metcalfe, ), and one case report (Gernart et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The predominant population of interest was patients (eight adult and one pediatric) with two studies looking at both adult and pediatric patients (Lee et al., ; Macpherson et al., ) and three studies not explicitly stating the age of the population impacted by the app (Cingi et al., ; Dickson et al., ; Lee et al., ). Five studies reviewed apps relating to healthcare clinicians including medical, nursing, social work, pharmacists, and clerical staff (Foo et al., ; Jakel et al., ; Khanna et al., ; Lee et al., ; Patel et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other research found in this review that described possible methods for improving care coordination in hospitals included literature that focussed on: the use of communications technology to improve clinical communications, [8] the effectiveness of quality improvement and other interventions taking place in acute care settings (a systematic review), [9] studies that considered the effectiveness of information display systems in hospitals, [10][11][12] studies that considered the use of electronic task management tools, [13,14] a study that considered the effectiveness of nurse clipboard design, [15] and one that looked at the effectiveness of using a secure messaging application in a hospital. [16] However, as a group, this research did not describe measurable improvements to patient outcomes or efficiency, instead focussing on results that: were process rather than outcome oriented (such as the extent of usage of tools, or impacts on team behaviours); were subjective (such as measures of user satisfaction and self-efficacy, attitudes towards teamwork, and perceptions of care); reported improvements that were not compared against any other measure; or were statistically non-significant.…”
Section: Resultsmentioning
confidence: 99%